EFEKTIVITAS BIROKRASI PEMERINTAHAN SEBAGAI LEGALITAS PEMBANGUNAN DEMOKRASI - rosa arista narendra (Universitas 17 Agustus 1945 Jakarta, 2017)
The bureaucracy exists to bridge the aspects of politics, power and the public interest against the control of the Government in carrying out policies that have direct access with the people. The bureaucracy that has a bad image for the face of Government has always been a discussion of materials to take sides in realizing the reform of the bureaucracy in Indonesia. Bureaucratic reform is expected in an effort to consolidate democracy, where the holder of a democracy can be felt by the people literally. The bureaucracy that is not neutrality affects the joints in the life of the nation and the State, because of its success in bureaucratic neutrality will be legality as the main element in a democratic development. Democratic development will according, if the existence of the effectiveness and efficiency of the bureaucracy that seems to threaten against the mechanisms of making all the decisions.